DYNAMIC GOVERNANCE DALAM MEWUJUDKAN KOTA DENPASAR SEBAGAI SMART CITY MELALUI PEMANFAATAN APLIKASI PRO DENPASAR+ - Febriantini, Komang Trisna; Yudharta, I Putu Dharmanu; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2021)
Denpasar Mayor Regulation Number 49 of 2019 is a reference to use PRO Denpasar+ application in realizing Denpasar City as a smart city in Indonesia. The process of transforming the governance through a smart city has indicated that Denpasar is implementing the practice of dynamic governance. The purpose of this study is to determine the dynamic governance process in realizing Denpasar as a smart city through the use of PRO Denpasar+ application using dynamic governance theory by Neo and Chen. This study was analyzed using a qualitative descriptive method which resulted in observation data, documentation, and in-depth interviews with informants. The results of this study is all indicators have entered into the dynamic capability process but in its implementation there are still deficiencies in indicators of thiking again because the problem of socialization that has not been carried out optimally which impacts to functions and number of application users. Keywords: Dynamic Governance, Smart City, PRO Denpasar+ Application